2018
DOI: 10.1089/zeb.2017.1559
|View full text |Cite
|
Sign up to set email alerts
|

Rearing Zebrafish on Black Soldier Fly (Hermetia illucens): Biometric, Histological, Spectroscopic, Biochemical, and Molecular Implications

Abstract: A desirable goal of the aquaculture sector is to replace most of fish meal and fish oil with more sustainable, cost-effective, and environmental friendly ingredients ensuring fish health and welfare standards. Due to minimal environmental impact, compared with most conventional feed commodities, insects deserve a growing attention as candidate ingredients for aquafeeds. The present study investigated, for the first time, the possible application of a 100% insect diet in zebrafish larval rearing. Through a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 84 publications
6
34
1
Order By: Relevance
“…In particular, Truzzi et al (2020) 9 demonstrated that the addition of a 10% (w/w) of Schizochytrium sp. to the growth substrate was an efficient method to enrich BSF final biomass in terms of PUFAs and to increase, with respect to previous studies on zebrafish, the BSF meal inclusion level in the fish diets without affecting fish welfare 21,29,33 . However, the potential of these enriched BSF prepupae as alternative feed ingredient for fish was evaluated only during the fish larval stage 19 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In particular, Truzzi et al (2020) 9 demonstrated that the addition of a 10% (w/w) of Schizochytrium sp. to the growth substrate was an efficient method to enrich BSF final biomass in terms of PUFAs and to increase, with respect to previous studies on zebrafish, the BSF meal inclusion level in the fish diets without affecting fish welfare 21,29,33 . However, the potential of these enriched BSF prepupae as alternative feed ingredient for fish was evaluated only during the fish larval stage 19 .…”
Section: Discussionmentioning
confidence: 77%
“…significantly increased insects' PUFAs content. With respect to previous studies carried out on zebrafish 21,29 , this enriching procedure allows to include up to 50% of BSF meal in the fish diet without impairing fish physiology, and hence represents a remarkable example of sustainable circular economy. Zebrafish represents an ideal organism to better understand fish physiological responses to new ingredients 30 and an emerging useful model organism for neuroscience/behavioural research 31 .…”
mentioning
confidence: 99%
“…Importantly, without defatting, it is not easy to use HF larvae in a marine-fish diet and obtain appropriate crude protein and lipid composition, since HF larvae have an excess of crude lipids (20-35%, dry matter) and markedly different fatty acid profiles than feeds made from wild fish. The fatty acid profile in black-soldier fly larvae (Hermetia illucens) was reported to affect lipid composition and accumulation in zebrafish (Danio rerio) [44,45]. Eliminating the hydrophobic faction is, therefore, an important first step in the development of HF larva-based feeds for marine-fish aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, studies on insect application in fish nutrition have continuously developed in terms of experimental data for new species, forms, and technologies of preparation of insect-derived feed materials (Tschirner et al, 2017;Gasco et al, 2019c). Insects were tested in the diet of farmed fish (Józefiak et al, 2019a;Józefiak et al, 2019b), ornamental species (Vargas-Abúndez et al, 2019), laboratory fish models (Vargas et al, 2018) as well as aquatic invertebrates (Motte et al, 2019). They are part of feeding practice in ornamental (James, 2019) fish feeding, as well as other aquatic and semiaquatic pets (Rawski et al 2018).…”
Section: Fishmentioning
confidence: 99%